2017
DOI: 10.1177/1073858417712668
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Axonal Transcriptome Brings New Functions for Axonally Synthesized Proteins in Health and Disease

Abstract: Intra-axonal protein synthesis has been shown to play critical roles in both development and repair of axons. Axons provide long-range connectivity in the nervous system, and disruption of their function and/or structure is seen in several neurological diseases and disorders. Axonally synthesized proteins or losses in axonally synthesized proteins contribute to neurodegenerative diseases, neuropathic pain, viral transport, and survival of axons. Increasing sensitivity of RNA detection and quantitation coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 176 publications
(285 reference statements)
0
33
0
Order By: Relevance
“…mRNAs, ribosomes, and other components of translational machinery are present in PNS axonal and CNS dendritic compartments [17,35,36]. Release of endogenous molecules associated with tissue damage increases nascent protein synthesis in DRG neurons and their axons via activation of signaling pathways upstream of translation (Figure 3).…”
Section: Local Mrna Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNAs, ribosomes, and other components of translational machinery are present in PNS axonal and CNS dendritic compartments [17,35,36]. Release of endogenous molecules associated with tissue damage increases nascent protein synthesis in DRG neurons and their axons via activation of signaling pathways upstream of translation (Figure 3).…”
Section: Local Mrna Translationmentioning
confidence: 99%
“…However, the identity of the full repertoire of mRNAs that are translated to lead to this change in excitability is only starting to emerge. While much of work has been done to identify mRNAs that localize to DRG axons in vitro [35], there are substantial technical challenges to confirm that these mRNAs localize to DRG axons in vivo . Nevertheless, several mRNAs have been localized to DRG axons in mice and rats, and some of these have been linked to pain hypersensitivity, such as the mRNAs for CREB, CPEB, and Na v 1.8 [38,39] (Table 2).…”
Section: Local Mrna Translationmentioning
confidence: 99%
“…The gene ontology (GO) analysis of the mRNAs enriched in axons compared with the soma reveals many shared GO terms (also analyzed in ref. []), including those related to translation, mitochondria, and cytoskeleton. Other categories are represented in some data sets, for example intracellular trafficking, axon guidance, and synaptic‐related proteins (Table ).…”
Section: Transcriptomic Translatomic and Proteomic Data Of Axons: Kmentioning
confidence: 99%
“…For some mRNAs, this localized translation imparts unique functions to the cell. As remarkably polarized cells with widely separated and specialized subcellular domains, neurons have provided a very useful model system to profile the populations of mRNAs that are transported into axons and dendrites as well as to test functions of proteins synthesized locally in these subcellular compartments (Kar et al, 2018;Terenzio et al, 2017). Indeed, axons can extend to lengths that are more than 1000-fold longer than the neuron's cell body diameter, and localized synthesis of new proteins in distal axons provides a level of autonomy to respond to extracellular stimuli (Sahoo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…RNA profiling studies have shown hundreds to thousands of mRNAs localized into axons of sensory, cortical, retinal ganglion cell, and motor neurons (Kar et al, 2018). These populations include several mRNAs encoding proteins that can impact the axonal cytoskeleton, either directly through generation of cytoskeletal proteins or indirectly by generation of proteins that regulate polymerization, depolymerization, severing or branching of the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%